The Neutra Participles Constructions with Genderless Pronouns in the Standard Lithuanian and Their Equivalents in Latvian - Valskys, Vidas (Kalbotyra, 2001)
This article presents a syntactic and semantic analysis of the predicative neutra participle constructions with viskas, niekas, kas, daug kas, tai, visa tai and other genderless pronouns in Lithuanian.Constructions of Standard Lithuanian are compared and contrasted with the corresponding Latvian constructions.